974 Improving Safety for Tracheostomy and Laryngectomy Patients Within A Regional Head and Neck Unit. (12th October 2021) - Simpson, L; Watson, G
Abstract: Aim: To improve the safety of tracheostomy and laryngectomy patients within a UK-based regional head and neck unit. Method: This audit was conducted against standards taken from the National Tracheostomy Safety Project (NTSP). Inclusion criteria were all patients with a tracheostomy or laryngectomy on the ward, there were no exclusion criteria. Data was collected per inpatient episode for a one month period pre- and post- implementation of each intervention (1st March to 31st May 2020). Results: Pre-intervention results showed that none of the 19 neck-breathing inpatients during March 2020 had a bedhead sign or emergency algorithm displayed, however all patients had required bedside equipment and the only unavailable ward equipment was capnography. Laminated bedhead signs and algorithms were implemented and 33% neck-breathing patients had signs displayed during April 2020. Further intervention in May 2020 to educate ward staff led to 90% of patients having a bedhead sign displayed and 80% having an algorithm displayed. Conclusions: Overall, our unit has very high standards of care for neck-breathing patients. The use of bedhead signs and emergency airway algorithms is an integral part of providing safe care for neck-breathing patients and all members of staff are responsible for their use. The COVID-19 crisis has impacted on the number of elective procedures being performed which has impacted upon the numbers for the post-intervention arms of our audit. Reduced staffing due to sickness during the pandemic may have contributed to the substandard results.